PENGARUH PEMBERIAN ZAT PENGATUR TUMBUH TERHADAP PERTUMBUHAN STUM MATA TIDUR KARET (Hevea brasiliensis Muell Arg.) KLON BPM 24 - ., Yuliantina; Usman, Eddy; Predita, Novran (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2015)
This research aimed to assess the effect of alternative plant growth regulators to the growth of stum dorman see rubber Klon BPM 24. This research was done at Lubung Saung Village, District And Banyuasin III Regency South Sumatera Province. This research used a randomized block design with five treatment and five replications. The treatments studied were B0 = 0 ml L-1 control, B1 = 2 ml L-1 of water, B3 = 6 ml L-1Â of water, B4 = 8 ml L-1Â of water. Each treatment consisted of 10 plants, with a long soaking the whole treatment was 15 minutes. Thus obtained 25 combined treatment. Each unit experiments were 3 examples of plans. Parameters namely speed sprout observations (HST), shoot length (cm), number of leak stalk (strands), the percentage of seedlings grown (%), weight wet plant (g),Â dry weight of plant (g), weight of wet roots departure (g), and root dry weight (g). Based on result obtained it can be concluded that, the concentration of growth regulators treatment 0f 8 ml L-1 water tends to give the highest yield and better seed to grow that percentage to 80 %, the speed of growth was 20.40 HST shoots, shoot length was 30.79 cm, weight was plants dry weight 7.10 g, wet weight was 1.94 g root, root dry weight was 0.88 g.